Reciprocal Teaching and Genre-Based Approach Combination: A Proposed Strategy in Business English Classes - Hariyanto, Sugeng (TEFLIN Journal, 2015)
Reciprocal teaching (RT) is a teaching procedure for reading comprehension involving direct instruction, modeling, feedback and repeated practice in four cognitive strategies, namely questioning, clarifying, summarizing, and predicting. The focus of Genre-based approach is to show students how meaning can be constructed with language and train them to make use of language to fulfill their needs. This approach proceeds through 4 steps: preparation, modelng, joint construction, independent construction, plus one additional step, publishing. Reciprocal teaching approach (RT) is used because it can incorporate speaking activities. The texts are selected based on the genre that will be used in the work sites, namely in the office setting. This article presents how to apply reciprocal teaching and genre-based approach to teach Business English at non-English Department of university level. This proposed strategy has been tried out at Business Administration Department of State Polytechnic of Malang. A sample lesson plan is given at the end of this article.